2021
DOI: 10.21203/rs.3.rs-349677/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Versus Late Use of Dexamethasone in Critically Ill Patients With COVID-19: A Multicenter, Prospective Cohort Study

Abstract: Background: Corticosteroids, especially dexamethasone, showed a survival benefit in critically ill COVID 19 patients. However, it is unclear whether the timing of dexamethasone initiation is associated with positive outcomes. The aim of this study is to evaluate the timing of dexamethasone initiation and 30-day ICU mortality in critically ill patients with COVID19. Methods: A multicenter, non-interventional, prospective study for all adult COVID19 admitted to intensive care units (ICUs) who received systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, it is reasonable to assume ACE2 variant rs2106809 T allele or some other SNPs in the same linkage disequilibrium block, may be functional and could decrease the sACE2 expression and increase the susceptibility to hypertension. Considering the double effect of sACE2 on hypertension and antiviral activity, this may partly explain the high incidence rate of hypertension (58%) in critically ill patients with COVID-19 (Sulaiman et al, 2021). By the way, ACE2 rs2074192 T allele and rs2285666 G allele, which are listed in the Table 2, have been reported to be associated with more severe clinical outcomes of SARS-CoV-2 infection (Cafiero et al, 2021;Mohlendick et al, 2021).…”
Section: Comorbidities and Ace2 Polymorphismsmentioning
confidence: 99%
“…Therefore, it is reasonable to assume ACE2 variant rs2106809 T allele or some other SNPs in the same linkage disequilibrium block, may be functional and could decrease the sACE2 expression and increase the susceptibility to hypertension. Considering the double effect of sACE2 on hypertension and antiviral activity, this may partly explain the high incidence rate of hypertension (58%) in critically ill patients with COVID-19 (Sulaiman et al, 2021). By the way, ACE2 rs2074192 T allele and rs2285666 G allele, which are listed in the Table 2, have been reported to be associated with more severe clinical outcomes of SARS-CoV-2 infection (Cafiero et al, 2021;Mohlendick et al, 2021).…”
Section: Comorbidities and Ace2 Polymorphismsmentioning
confidence: 99%
“…However, many researchers pointed out that, in practice, the symptom onset is usually impossible to ascertain, and the signs of severity often appear late. In a study that assessed the association between the dexamethasone initiation time and mortality benefits, Sulaiman et al (2021) found survival benefits with the early initiation in critically ill COVID-19 patients [26]. The WHO panel concluded that it is preferable that critical COVID-19 patients receive corticosteroids (even if within 7 days of symptom onset) but noncritical patients do not (even if after 7 days of symptoms onset) [27].…”
Section: Introductionmentioning
confidence: 99%